The Implementation of Lesson Study in English Language Learning: A Case Study - Nashruddin, Wakhid; Nurrachman, Dian (Dinamika Ilmu, 2016)
Lesson Study as a growing interest in the education world has attracted educators, experts, and professionals in the area to make use of it in improving the lessons—it also happens in Indonesia. Originally applied in the teaching of mathematics in Japan, now it turns to be used in other fields, and English is one of them. This paper highlights the guideline on Lesson Study and pictures its application in a private senior high school in Malang, East Java, Indonesia. The adaptation of Lesson Study is interesting since Japan and Indonesia have different cultural background. How Lesson Study is usually implemented in Japan and the US and how it is applied in Indonesia will be seen here. As this is a case study, it will only focus on a school and the result should not be used to generalize Lesson Study applications in Indonesia. Interview and observation were instruments used in this study. The interview was used to gain information on how Lesson Study was normally conducted and observation (and the researchers’ involvements) was used to see the real implementation of Lesson Study. What happened during the implementation of Lesson Study and during the teaching and learning process become a great attention here.